Exploração racional da rede metabólica de Xylaria sp. visando à produção de metabólitos de interesse farmacológico através de ferramentas quimiométricas e técnicas de desreplicação - Vieira, Rafael [UNESP] (2015)
This work has as its main focus, analyze the behavior of the fungus Xylaria sp. before physicochemical variations via the OSMAC approach (One Strain, Compounds Many). To achieve such induction and exploit the variability of the metabolic network of this micro-organism, a factorial design was designed to induce variability (or potentiating) metabolites. Before chemometric backrests, planned inductions were imposed on the micro-organism and it was observed variations in the chemical profile in crude extracts. Added to this, dereplication techniques were used to study the chemically complex matrices produced by this fungus aimed at producing high added value and metabolites was determined specific conditions for the production of molecules cytochalasin D and griseofulvin.